ASPEK HUKUM KEPAILITAN KOPERASI DI SEKTOR JASA KEUANGAN - Wahyu Maylaffayza Nandine Firdausi; Kukuh Leksono Suminaring Aditya (Veritas et Justitia, 2025)
The enactment of Law Number 4 of 2023 introduces a new category of cooperatives, namely Cooperatives in the Financial Services Sector. These cooperatives are permitted to receive funding exceeding 40 percent of their total assets from external parties while engaging in financial services activities. As a consequence, the Financial Services Authority (Otoritas Jasa Keuangan/OJK) is designated as the supervisory authority for such cooperatives. Accordingly, when Cooperatives in the Financial Services Sector experience financial distress resulting in default, their creditors may file bankruptcy petitions against them. However, such petitions cannot be submitted directly to the Commercial Court. Article 8B of Law Number 4 of 2023 requires that bankruptcy petitions be submitted first to the OJK for evaluation. Despite this requirement, there is currently an absence of detailed regulations governing the procedural mechanism for filing such petitions. This research employs a normative legal method using statutory and conceptual approaches. The study finds that creditors may submit bankruptcy petitions against cooperatives to the OJK, which is required to evaluate the petition within 45 days. If the cooperative is deemed unable to fulfill its debt obligations, the OJK will forward the petition to the Commercial Court for bankruptcy proceedings. Ultimately, the Government may dissolve the cooperative if its continued operation can no longer be reasonably expected due to insolvency.